Development of a data registry to evaluate the quality and safety of nursing practice. (6th March 2019) - Sim, Jenny; Joyce‐McCoach, Joanne; Gordon, Rob; Kobel, Conrad
Abstract: Aim: To describe the development, testing, and implementation of a data registry of nursing‐sensitive indicators for measuring the quality and safety of nursing practice. Background: Recent research has established causal links between nurse staffing and patient outcomes. Unit level data is necessary for implementation of evidence‐based strategies on nurse staffing and nursing care processes. Design: Multi‐site, cross‐sectional design. Methods: Retrospective data were collected from administrative data sets on nurse staffing, patient flow, and adverse events in three hospitals in 2016. Periodic observational surveys on pressure injury prevalence, hand hygiene practices, and documentation of processes of care were also conducted. Prospective data were collected from patients at time of discharge using the Caring Assessment Tool. Nurses' perceptions of their practice environment were assessed using the Nursing Work Index – Revised: Australian. Data from annual Press Ganey ® surveys on patient satisfaction/experience were obtained. Results: The Australian Nursing Outcomes Collaborative (AUSNOC) data registry was developed in three phases. Phase 1 involved development of a data codebook; phase 2 involved development and testing of data collection methods; and phase 3 involved development of data reports and data dissemination strategies. This paper gives an overview of these phases and includes a summary of the descriptive statistics from the indicator set. Conclusion: Unit level data is pivotal for measuring the quality and safety of nursing care. Data from the Australian Nursing Outcomes Collaborative (AUSNOC) can be feasibly collected and used to benchmark nursing performance, evaluate patient outcomes, and identify areas for practice improvement. Abstract : 目的: 说明护理敏感指标数据登记表中的开发、测试和实施部分, 以衡量护理实践的质量和安全性。 背景: 最近的研究已经建立了护士人员配置和患者恢复结果之间的关系。单位水平数据对实施以证据为基础的护理人员配置和护理流程策略非常必要。 设计: 多站点、横向设计。 方法: 评估性数据收集自2016年3家医院护士人员配备、患者流量、不良事件管理数据集。此外, 还定期对压力性损伤患病率、手部卫生习惯和护理过程文件进行了观察调查。前瞻性数据通过使用护理评估工具收集自出院患者。 通过《护理工作指数》(修订版:澳大利亚)评估护士对其实践环境的看法。从每年Press Ganey®患者满意度或经验调查中获取数据。 结果: 澳大利亚护理结果协作(AUSNOC)数据登记分三个阶段进行。第一阶段关于数据码本的开发;第二阶段关于数据收集方法的开发和测试;第三阶段关于数据报告和数据传播策略的开发。本文提供了这些阶段概述, 并总结了指标集的描述性统计数据。 结论: 单位水平数据是衡量护理质量和安全性的关键。可以收集澳大利亚护理结果协作(AUSNOC)的数据, 用于评估护理绩效、评估患者恢复结果和确定实践改进领域。